2012
DOI: 10.1007/s10072-012-1054-5
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual syndrome and migraine

Abstract: Premenstrual syndrome (PMS) includes a wide variety of physical, psychological, and cognitive symptoms that occur recurrently and cyclically during the luteal phase of the menstrual cycle and disappear soon after the onset of menstruation. Headache, often of migrainous type, is one of physical symptoms often reported in the diagnostic criteria for PMS. Menstrual migraine (MM) is a particular subtype of migraine occurring within the 2 days before and the 3 days after the onset of menses. According to this defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…In addition, headache practitioners should consider patient comorbidities, as some of the CAM therapies have been used in other circumstances and may therefore offer a twofold benefit. For example, patients with menstrual migraine and premenstrual syndrome may experience relief of both conditions with magnesium, phytoestrogens or ginkgolide B (129). In this way, clinicians need to weigh the 1128 Cephalalgia 36 (12) risks and benefits from the evidence, and consider individual patient characteristics and preferences when prescribing CAM, in the same manner as is currently the standard with pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, headache practitioners should consider patient comorbidities, as some of the CAM therapies have been used in other circumstances and may therefore offer a twofold benefit. For example, patients with menstrual migraine and premenstrual syndrome may experience relief of both conditions with magnesium, phytoestrogens or ginkgolide B (129). In this way, clinicians need to weigh the 1128 Cephalalgia 36 (12) risks and benefits from the evidence, and consider individual patient characteristics and preferences when prescribing CAM, in the same manner as is currently the standard with pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…COMT contains the common functional polymorphism, a G‐to‐A transition at codon 158, which results in a valine‐to‐methionine substitution (Val158Met, rs4680). Individuals homozygous for the mutation Val158Met show the three‐ to four‐fold reduced COMT activity in peripheral red blood cells , liver , and brain . COMT polymorphisms have been implicated in the pathogenesis of neuropsychiatric disorders associated with dopamine, such as schizophrenia, bipolar affective disorder, and Parkinson's disease .…”
Section: Discussionmentioning
confidence: 99%
“…Another open-label preliminary study found that modified-release magnesium 250 mg tablet was effective in improving PMS symptoms in affected women [29]. Additionally, magnesium was shown to have some efficacy in treating menstrual migraines that occur with PMS [30]. However, a case-control study that assessed mineral intake using questionnaires found that while nonheme iron, potassium, and zinc affected PMS risk, magnesium was unrelated to PMS [31].…”
Section: Premenstrual Syndromementioning
confidence: 99%